Pencapaian Pelajar dalam Mata Pelajaran Geografi Sekolah Menengah di Sabah – Analisis Awal (Sains Humanika, 2017)
This study intends to examine student achievement in subject of geography. This studyinvolves variables of attitudes, interest, teacher’s role and parents’ role with student achievement. This is a preliminary study involved only one district in Sabah, Kota Marudu district. Data were collected through a questionnaire which contains 40 items to measure, attitude, interest, teacher’s role and parents’ roles. Meanwhile, final examination results year 2015 used to measure student achievement for geography subject. A total of 257 Form Five students representing six schools that took geography involved in this study were selected through random sampling. Data were analysed using SPSS software by selecting the Pearson correlation analysis. Research finding showed that students’ attitude has a significant relationship with student achievement. Meanwhile, interest, teacher’s roles and parents' roles have no relationship with student achievement. The findings gave implications for the abolition of geography subjects if student achievement still remained in low-level. Hence, teachers and parents play an important role to form a high interest and a more positive attitude towards students in order to improve their achievement in subject of geography.
Keywords: Attitude; interest; role of teacher; parents' role; achievement